Long-term trends and projections of stomach cancer burden in China: Insights from the GBD 2021 study - Zhouwei Zhan; Bijuan Chen; Yi Zeng; Rui Huang; Jiami Yu; Zengqing Guo; Xiaoyan Lin (PLoS ONE, 2025)
Stomach cancer continues to be a major public health concern in China, with its incidence, prevalence, mortality, and overall burden showing notable changes over time. This study set out to analyze the long-term trends of stomach cancer from 1990 to 2021, figure out the effects of aging, epidemiological changes, and population growth, and also make projections for the future. To conduct the study, data from the Global Burden of Disease Study 2021 was used. This data allowed for the analysis of various aspects such as age-standardized incidence, prevalence, mortality rates, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs) related to stomach cancer in China. Joinpoint regression analysis was carried out to spot significant trends and turning points. Decomposition analysis was done to assess how much aging, epidemiological changes, and population growth contributed. Additionally, the Bayesian age-period-cohort (BAPC) model was employed to predict what the trends might be from 2021 to 2030. In 2021, there were 611,799 new cases of stomach cancer in China. The age-standardized incidence rate was 29.05 per 100,000 people, with males having a much higher rate of 44.48 compared to females at 15.23. The age-standardized prevalence and mortality rates were 57.22 and 21.51 per 100,000 respectively, and both were higher in males as well. There were also significant gender differences in DALYs, YLDs, and YLLs, with males shouldering a greater burden. From 1990 to 2021, the incidence and mortality rates went down, especially after 2004. Through decomposition analysis, it was found that aging led to a decrease in incidence but an increase in mortality, especially among males. Epidemiological changes caused both the incidence and mortality rates to drop, and the effect was more pronounced in males. The BAPC model forecasts that the incidence and mortality rates will continue to decline for both genders from 2021 to 2030, with a more rapid decrease in males. Overall, this study emphasizes the changing trends of the stomach cancer burden in China, the significant gender differences, and the impacts of aging, epidemiological changes, and population growth. It’s crucial to keep monitoring and implement targeted public health strategies to further reduce the burden of stomach cancer.